2010 5th International Conference on Computer Science &Amp; Education 2010
DOI: 10.1109/iccse.2010.5593755
|View full text |Cite
|
Sign up to set email alerts
|

Mining positive and negative association rules

Abstract: Association rule mining is one of the most popular data mining techniques to find associations among items in a set by mining necessary patterns in a large database. Typical association rules consider only items enumerated in transactions. Such rules are referred to as positive association rules. Negative association rules also consider the same items, but in addition consider negated items (i.e. absent from transactions). Negative association rules are useful in market-basket analysis to identify products tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…According to [25] the positive and negatives rules gives better classification accuracy thus helps in reasoning with less classification time. Moreover, [26] highlighted the importance of NAR besides PAR where better decision can be made especially in devising marketing strategies. Figure 1 describes the flowchart of the hybridized method.…”
Section: The Proposed Hybrid Rough_negative Algorithmmentioning
confidence: 99%
“…According to [25] the positive and negatives rules gives better classification accuracy thus helps in reasoning with less classification time. Moreover, [26] highlighted the importance of NAR besides PAR where better decision can be made especially in devising marketing strategies. Figure 1 describes the flowchart of the hybridized method.…”
Section: The Proposed Hybrid Rough_negative Algorithmmentioning
confidence: 99%
“…Studies over NAR have shown that the rule is effective, efficient and promising algorithm [34,35]. NAR is also use to interpret meaningful knowledge from the rules of information systems [36,46].…”
Section: Negative Association Rulesmentioning
confidence: 99%
“…NAR is also use to interpret meaningful knowledge from the rules of information systems [36,46]. According to [34] mining PAR and NAR rules is useful for constructing associative classifiers following the supportconfidence framework as in Association Rules mining. By using the framework, no extra scan is required to mine NAR rules.…”
Section: Negative Association Rulesmentioning
confidence: 99%
“…In paper [4], they proposed Associative classification which is a classification of a new tuple using association rules. It is a combination of association rule mining and classification.…”
Section: Literature Reviewmentioning
confidence: 99%